Professionalism : what does it mean to you? : the employees' view of professionalism. - Seow, Ruqing. (2010)
There has been an increased awareness of the importance of being professional in organizations. This study aims to examine employees’ perspective on the meaning of professionalism and resultant attitudes and behaviours from seeing oneself as being “professional”. Additionally, suggestions from employees for supporting professionalism in organizations are also examined. Two qualitative methods were used for data collections which included 20 interviews and a focus group discussion with six taxi drivers in Singapore. Our findings indicate that the nature of job, possession of specialized skills/knowledge, and positive working attitude are the main ideas of what professionalism means. Additionally, when employees perceive themselves as professionals, they will react by putting their company’s interest first, having integrity, exhibiting positive work attitudes and self image, as well as cooperative behaviours. Finally, the participants feel that providing training and setting good examples and clear guidelines are effective measures to support professionalism. The participants also felt that professionalism may bring benefits such as better company’s image and profitability. Thus, this research acts as a platform for organizations to look at promoting professionalism.